COMMUNITY STRUCTURE OF GASTROPODS IN THE COASTAL WATERS OF NORTH RUPAT DISTRICT - Pertika, Dinda; Nasution, Syafruddin; Tanjung, Afrizal (Asian Journal of Aquatic Sciences, 2022)
Community structure is a concept that studies the composition or composition of species and abundance in a community. Coastal waters are areas with a depth of less than 200 meters and there is a littoral area located between the highest tide and the lowest low tide or called the intertidal area. One of the community of organisms in this intertidal area is gastropods. This research was conducted from December 2021 to January 2022. The purpose of the study was to determine the structure of the gastropod community in the coastal waters of North Rupat District consisting of species, density, diversity index, uniformity index, dominance index, distribution pattern, and community similarity. As supporting data in this study, several environmental parameters were also measured which included water quality, sediment type and sediment organic matter content. The research method used is a survey method, where sampling using the quadrant transect method is carried out at 3 stations. Based on the results of the study found 14 species of gastropods. The species that were found in all stations were Indothais gradata. Gastropod density is 15.800 ind/ha. Diversity index value (H') 1.85, uniformity index (E) 0.70, dominance index (C) 0.24, distribution pattern (Id) 3.24 is clustered, species similarity index (Ss) between stations Tanjung Medang and Teluk Rhu 83% of species are almost the same and between stations Tanjung Medang and Tanjung Punak 15% and between stations Teluk Rhu and Tanjung Punak 17% are not the same. Water quality parameters as follows: temperature 27-28oC; salinity 30-31 ppt; pH 6-7. Sediment organic matter 0.50-2.28%, sand sediment type.